2021
DOI: 10.1093/nar/gkab684
|View full text |Cite
|
Sign up to set email alerts
|

Ribosome-binding and anti-microbial studies of the mycinamicins, 16-membered macrolide antibiotics from Micromonospora griseorubida

Abstract: Macrolides have been effective clinical antibiotics for over 70 years. They inhibit protein biosynthesis in bacterial pathogens by narrowing the nascent protein exit tunnel in the ribosome. The macrolide class of natural products consist of a macrolactone ring linked to one or more sugar molecules. Most of the macrolides used currently are semi-synthetic erythromycin derivatives, composed of a 14- or 15-membered macrolactone ring. Rapidly emerging resistance in bacterial pathogens is among the most urgent glob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…But for P. aeruginosa , the peptidoglycan layer of the cell wall is thin, the cross-linking is loose, and the lipid content is high ( Rajivgandhi et al, 2018 ). Higher lipid content within the cell wall of P. aeruginosa made LSL easier to fuse with, thus preventing the formation of a new cell wall and destroying the cell membrane structure ( Breiner-Goldstein et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…But for P. aeruginosa , the peptidoglycan layer of the cell wall is thin, the cross-linking is loose, and the lipid content is high ( Rajivgandhi et al, 2018 ). Higher lipid content within the cell wall of P. aeruginosa made LSL easier to fuse with, thus preventing the formation of a new cell wall and destroying the cell membrane structure ( Breiner-Goldstein et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…108 The structures of mycinamicins I (110), II (112), and IV (113) suggested that these antibiotics could bind the ribosome in a similar orientation as other AGs, and their C12−C14 substituents played an important role in their special MOAs since they may interact with the nascent chain in a differential manner. 119 The BGC of compound 112 in M. griseorubida A11725 contained 22 open reading frames (ORFs) and was first characterized by Kato and co-workers (Figure 9). 120 The robust de novo synthesis of the 16-membered macrolide mycinamicin IV (113) was achieved through the systematic screening of the glycosidation promoter using a collective approach (Scheme 2).…”
Section: Bioactive Secondary Metabolites Ofmentioning
confidence: 99%
“…rosaria as a new macrolide containing a unique pyridine ring, and erythromycin ( 109 ) was first reported to be isolated from Micromonospora species . The structures of mycinamicins I ( 110 ), II ( 112 ), and IV ( 113 ) suggested that these antibiotics could bind the ribosome in a similar orientation as other AGs, and their C12–C14 substituents played an important role in their special MOAs since they may interact with the nascent chain in a differential manner …”
Section: Bioactive Secondary Metabolites Of Micromonosporamentioning
confidence: 99%
“…Such antibiotics can be used as a potential alternative approaches for treatment in the clinic. According to traditional understanding, 16-membered ring macrolides can’t induce the expression of resistance genes [ 12 ]. With increasing research, it was found that 16-membered ring macrolides could also induce the expression of resistance genes.…”
Section: Introductionmentioning
confidence: 99%